Radio-immunomics in hepatocellular carcinoma: Unraveling the tumor immune microenvironment - Qianyun Liu; Wenwei Zhu; Fulong Song; Tuo Lou; Lei He; Wenming Zhou; Zhichao Feng (Meta-Radiology)
Hepatocellular carcinoma (HCC) ranks as the sixth most prevalent and the fourth most lethal malignancy worldwide, frequently manifesting at advanced stages with limited therapeutic options. Despite notable therapeutic advancements, challenges persist in precisely identifying patients likely to respond to immune-checkpoint inhibitors (ICIs). The tumor immune microenvironment (TIME) plays a pivotal role in the biological behavior of HCC, necessitating non-invasive methods for a comprehensive assessment prior to treatment initiation. Spatiotemporal molecular medicine, particularly radio-immunomics, emerges as a promising approach through integrating multi-omics data to decode the TIME. This review delineates the intricate TIME characteristics of HCC, summarizes recent advancements in radiomics for immune profiling within the framework of spatiotemporal molecular medicine, and delves into challenges and future prospects of radio-immunomics, highlighting the dynamic interplay of radiomics, genomics, and immunobiology. The evolving field of radio-immunomics holds unparalleled potential for non-invasive, personalized characterization of TIME in HCC, providing avenues to inform tailored treatments and optimize patient outcomes.